The Establishment of Diplomatic Relations Between the Russian Empire and the Kingdom of Portugal - D. N. Ermolovich (Ибероамериканские тетради)
Russia and Portugal established diplomatic relations relatively late. Some researchers indicate geography as the main cause; however, geography alone could hardly explain why, for instance, the Russian Empire established official relations with Spain approximately sixty years before it did with the Portuguese Royal Court. As it seems, the international situation and factors related to both states’ domestic development were at play. Back in the late 15th and early 16th centuries, Portugal considered regions far beyond Europe, such as South America, Africa, India and the Far East to be its sphere of interests. As a result, the country’s limited resources, combined with the need to ensure the preservation of the vast colonial empire, predetermined its dependence on Great Britain for defense. In the 18th century, the costs of such dependence outweighed the potential benefits. Meanwhile, Russia in the 18th century was a powerful and dynamic state which sought to change the traditional balance of power in Europe and develop maritime trade. The idea of establishing relations with Portugal was already considered under Peter I, yet it was not until late 18th century that the Russian Empire succeeded under Catherine II. The geographical factor did have a significant impact on delaying mutual recognition; still it was the two countries’ converging interests and the favorable international situation that proved to be crucial.